STOML2 interacts with PHB through activating MAPK signaling pathway to promote colorectal Cancer proliferation - Wenhui Ma (BMC, 2021)
Abstract Background Highly expressed STOML2 has been reported in a variety of cancers, yet few have detailed its function and regulatory mechanism. This research aims to reveal regulatory mechanism of STOML2 and to provide evidence for clinical therapeutics, via exploration of its role in colorectal cancer, and identification of its interacting protein. Methods Expression level of STOML2 in normal colon and CRC tissue from biobank in Nanfang Hospital was detected by pathologic methods. The malignant proliferation of CRC induced by STOML2 was validated via gain-of-function and loss-of-function experiments, with novel techniques applied, such as organoid culture, orthotopic model and endoscopy monitoring. Yeast two-hybrid assay screened interacting proteins of STOML2, followed by bioinformatics analysis to predict biological function and signaling pathway of candidate proteins. Target protein with most functional similarity to STOML2 was validated with co-immunoprecipitation, and immunofluorescence were conducted to co-localize STOML2 and PHB. Pathway regulated by STOML2 was detected with immunoblotting, and subsequent experimental therapy was conducted with RAF inhibitor Sorafenib. Results STOML2 was significantly overexpressed in colorectal cancer and its elevation was associated with unfavorable prognosis. Knockdown of STOML2 suppressed proliferation of colorectal cancer, thus attenuated subcutaneous and orthotopic tumor growth, while overexpressed STOML2 promoted proliferation in cell lines and organoids. A list of 13 interacting proteins was screened out by yeast two-hybrid assay. DTYMK and PHB were identified to be most similar to STOML2 according to bioinformatics in terms of biological process and signaling pathways; however, co-immunoprecipitation confirmed interaction between STOML2 and PHB, rather than DTYMK, despite its highest rank in previous analysis. Co-localization between STOML2 and PHB was confirmed in cell lines and tissue level. Furthermore, knockdown of STOML2 downregulated phosphorylation of RAF1, MEK1/2, and ERK1/2 on the MAPK signaling pathway, indicating common pathway activated by STOML2 and PHB in colorectal cancer proliferation. Conclusions This study demonstrated that in colorectal cancer, STOML2 expression is elevated and interacts with PHB through activating MAPK signaling pathway, to promote proliferation both in vitro and in vivo. In addition, combination of screening assay and bioinformatics marks great significance in methodology to explore regulatory mechanism of protein of interest.